PERAN KOMUNIKASI DALAM DEMOKRATISASI - Lukmantoro, Triyono (FORUM)
abstract: Communication has a vital role in the processes of democratization. But, on the other perspective, democracy also determines the way of communication. There are three types of relations between communication and democracy: minimalist democracy, radical democracy, and deliberative democracy. We have to take the choice what kind of democracy that we think it is the best for us. Â Keywords: communication, democratization, types of democracy.permalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3205